Transformasi Digital untuk Meningkatkan Efisiensi Industri Rumah Tangga Dumbeg - Alliyah, Siti; Muniroh, Hetty; Hanantyo, Burhanuddin; Mahmudi, A. Aviv; Dewi, Nurma Gupita (Forum Kerjasama Pendidikan Tinggi, 2025)
The Community Partnership Empowerment Program was implemented to enhance production capacity, management efficiency, and marketing competitiveness of the traditional food home industry (IRT) producing dumbeg in Pohlandak Village, Pancur District, Rembang Regency. Dumbeg is a traditional local culinary product with high economic potential; however, the partner group still faces several challenges. The main problems include manual production processes that reduce efficiency, poorly organized business management, and conventional marketing systems that have not yet adopted digital technology. To address these challenges, the program applied a digital transformation approach through several implementation methods, including the development of appropriate technology in the form of a stainless-steel mixing machine to improve productivity and hygiene, entrepreneurship training based on creativepreneurship to strengthen business management capacity, and digital marketing through social media and e-commerce platforms. The program also produced innovations such as a web-based Sales Information System (SIP) and an e-commerce platform called “Omah Dumbeg” as tools for online promotion and transactions. The results showed an increase in production capacity from 200 to 300 units per day, a rise in turnover by approximately 10%, and an improvement in digital literacy among group members by 80%. This program has proven effective in enhancing efficiency, self-reliance, and business sustainability based on local potential in Rembang Regency through the implementation of digital transformation.